Effect of Thermal Cycling on Thermal Conductivity of Powder Injection Moulded MWCNT Reinforced Copper Matrix Composites - Ahmad, F. (Springer, 2020)
Thermal management of electronics is a great challenge to achieve optimum performance. Nano materials provide a pathway to increase thermal conductivity but nano particles uniform dispersion in the matrix is very difficult. This study focuses on dispersion of functionalized multi-walled carbon nano tubes in copper to improve thermal conductivity of copper. Copper/Carbon Nano Tubes (CNTs) composites were developed via powder injection moulding. Feedstock was compounded using Z-blade mixer and defect free green parts were produced by injection moulding. Binder was removed by solvent and thermal means followed by sintering in argon at 1050Â â. Thermal conductivity and reliability tests were performed on sintered nano composite specimen at various temperatures. Results showed good dispersion of CNTs in copper and thermal conductivity measured was 550â580Â w/m.k. A decrease of 27â37 in thermal conductivity was recorded during thermal cycling of sintered composite and the reduced thermal conductivity value is still 80 higher than pure copper. Â© 2020, Springer Nature Singapore Pte Ltd.